(untitled) (Economic studies journal, 2018)
The objective of this study is to analyze the extent to which credit decision makers in Libyan commercial banks are aware of the financial ratios of liquidity ratios, profitability ratios, ratios of financing structure and activity ratios when making a decision to grant credit. The researchers used a questionnaire form, The virtual credit officials were passed on to commercial banks sample study. The study showed that credit officers in commercial banks are not aware of the financial ratios of liquidity, ratios of financing structure and rates of activity, and that they are aware of profitability ratios. The study recommended the need to raise credit officials by giving them training courses.